Comorbidity Index as a Predictor of Mortality in Pediatric Patients With Solid Tumors - Torres-Espíndola, Luz María; Demetrio-Ríos, Joel; Carmona-Aparicio, Liliana; Galván-Díaz, César; Pérez-García, Martín; Chávez-Pacheco, Juan Luís; Granados-Montiel, Julio; Torres-Ramírez de Arellano, Israel; Aquino-Gálvez, Arnoldo; Castillejos-López, Manuel De Jesús (Frontiers in Pediatrics, 2019)
Purpose: The objective of this study was to determine whether a comorbidity index could be used to predict mortality in paediatric patients with chemotherapy-treated solid tumours. Methods: Paediatric patients who underwent chemotherapy treatment for solid tumours were included, and demographic, clinical and comorbidity data were obtained from patient electronic records. Results: A total of 196 paediatric patients with embryonic solid tumours were included. Metastatic tumours were the most frequently observed (n=103, 52.6%). The most common comorbidities encountered for the Charlson comorbidity index (CCI) were cellulitis (n=24, 12.2%) and acute renal failure (n=15, 7.7%). For the Paediatric Comorbidity Index (PCI), the most frequent comorbidities were pneumonia and sepsis, with n=64 (32.7%) for each. We evaluated established the prognostic values for both indexes using Kaplan-Meier curves, finding that the CCI and PCI could predict mortality with p<0.0001. Conclusion: Using the PCI, we observed 100% survival in patients without comorbidities, 70% survival in patients with a low degree of comorbidity, and 20% survival in patients with a high degree of comorbidity. Greater discrimination of probability of survival could be achieved using degrees of comorbidity on the PCI than using degrees of comorbidity on the CCI. The application of the PCI for assessing the hospitalized paediatric population may be of importance for improving clinical evaluation.